2019
DOI: 10.1111/jocn.14999
|View full text |Cite
|
Sign up to set email alerts
|

“Juggling many balls”: Working and studying among first‐year nursing students

Abstract: Aims and objectives To explore the experiences of first‐year nursing students, their motivations for working and how they juggled study and other commitments while engaging in paid work. Background There has been a global rise in the number of students balancing full‐time study, paid work and other commitments, with the main antecedent financial reasons. Design Qualitative exploratory study. Methods Drawn from a larger Australasian sequential exploratory mixed‐method study, this qualitative study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(49 reference statements)
0
11
0
1
Order By: Relevance
“…Lo anterior coincide con los hallazgos de este estudio, en especial con los relatos sobre las motivaciones. En ella se define la independencia económica como uno de los motores que impulsa al estudiante a realizar ambas actividades, de la misma manera que señalan otros autores 18 .…”
Section: Experimentar Costosunclassified
“…Lo anterior coincide con los hallazgos de este estudio, en especial con los relatos sobre las motivaciones. En ella se define la independencia económica como uno de los motores que impulsa al estudiante a realizar ambas actividades, de la misma manera que señalan otros autores 18 .…”
Section: Experimentar Costosunclassified
“…The practicum in Australia is unpaid and is organised as a full-time commitment, thereby restricting students’ ability to undertake paid work. Australian data from 2005 to 2018 (inclusive) reveal over 70% of domestic undergraduate students were engaged in full time paid work [ 19 ], with a study of undergraduate nurse students reporting the primary reason behind the decision to engage in paid work during the degree as financial, with students citing mortgage repayments and family support as major driving factors [ 20 ]. A further study, this time with 160 nurse students at a single Australian university, reported “the majority of students struggle(d) financially during clinical placements” ([ 21 ] p.1).…”
Section: Introductionmentioning
confidence: 99%
“…The university years can be a challenging life stage for students [ 1 ]. Many students struggle to juggle academic demands and study–life balance [ 2 ], in addition to worries about securing a job in a competitive market [ 3 ]. Such difficulties are particularly true in challenging specialties such as medical or health-based fields [ 4 ].…”
Section: Introductionmentioning
confidence: 99%